Magnetic resonance spectroscopy evidence for declining gliosis in MS patients treated with ocrelizumab versus interferon beta-1a. Issue 4 (October 2019) - MacMillan, Erin L; Schubert, Julia J; Vavasour, Irene M; Tam, Roger; Rauscher, Alexander; Taylor, Carolyn; White, Rick; Garren, Hideki; Clayton, David; Levesque, Victoria; Li, David KB; Kolind, Shannon H; et al.
Background: Magnetic resonance spectroscopy quantitatively monitors biomarkers of neuron-myelin coupling (N-acetylaspartate (NAA)), and inflammation (total creatine (tCr), total choline (tCho), myo-inositol (mI)) in the brain. Objective: This study aims to investigate how ocrelizumab and interferon beta-1a differentially affects imaging biomarkers of neuronal-myelin coupling and inflammation in patients with relapsing multiple sclerosis (MS). Methods: Forty patients with relapsing MS randomized to either treatment were scanned at 3T at baseline and weeks 24, 48, and 96 follow-up. Twenty-four healthy controls were scanned at weeks 0, 48, and 96. NAA, tCr, tCho, mI, and NAA/tCr were measured in a single large supra-ventricular voxel. Results: There was a time × treatment interaction in NAA/tCr ( p  = 0.04), primarily driven by opposing tCr trends between treatment groups after 48 weeks of treatment. Patients treated with ocrelizumab showed a possible decline in mI after week 48 week, and stable tCr and tCho levels. Conversely, the interferon beta-1a treated group showed possible increases in mI, tCr, and tCho over 96 weeks. Conclusions: Results from this exploratory study suggest that over 2 years, ocrelizumab reduces gliosis compared with interferon beta-1a, demonstrated by declining ml, and stable tCr and tCho. Ocrelizumab may improve the physiologic milieu by decreasing neurotoxic factors that are generated by inflammatory processes.